2022
DOI: 10.1007/s00217-021-03944-2
|View full text |Cite
|
Sign up to set email alerts
|

Texture profile analysis and sensory evaluation of commercially available gluten-free bread samples

Abstract: The need for better quality gluten-free (GF) bread is constantly growing. This can be ascribed to the rising incidence of celiac disease or other gluten-associated allergies and the widespread incorrect public belief, that GF diet is healthier. Although there is a remarkable scientific interest shown to this topic, among the numerous studies only a few deals with commercially available products. The gap between research and commercial reality is already identified and communicated from a nutritional point of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 36 publications
0
14
0
1
Order By: Relevance
“…Springiness is a parameter used to define the freshness of the product and results in a more or less brittle crumb [ 64 , 65 ]. It is a measure of elasticity [ 66 ] and it is defined as the rate at which a deformed sample returns to its original size and shape [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Springiness is a parameter used to define the freshness of the product and results in a more or less brittle crumb [ 64 , 65 ]. It is a measure of elasticity [ 66 ] and it is defined as the rate at which a deformed sample returns to its original size and shape [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cohesiveness represents the extent to which the sample could be deformed before breaking [ 69 ], indicating the strength of the internal bonds in the sample [ 67 ]. It is related to the moisture content and the strength of the network surrounding the crumb cells [ 70 ], and in fact, low values of cohesiveness result in a bread with a crumb that crumbles easily [ 64 , 71 ]. From Table 5 , it can be noted that at T 0 , cohesiveness in the samples with bract flour increased as the percentage of integration increased, while in the samples with stems and mixes, the values significantly decreased ( p ≤ 0.001) from 5 to 10% integration.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, assessors highlighted its ‘homemade’ appearance. The aim of comparing commercial products already available on the market with novel food formulations is to ensure that they really have distinctive sensory characteristics (Tóth et al ., 2022). Overall, the results of the sensory analysis showed that the novel bread formulations containing nuts and legumes differed from the standard gluten‐free (STD) formulation as well as from a commercial product.…”
Section: Resultsmentioning
confidence: 99%
“…Judges were trained by discussing the definition of quality attributes selected for sensory evaluation such as leavening, taste, texture, appearance, aroma and general acceptability, explaining, and method of scoring. They were advised to rinse their mouth with water between tasting the consecutive samples (Tóth et al, 2022).…”
Section: Methodsmentioning
confidence: 99%